Economic impact of resident and nonresident marine anglers to the local economy in Mecklenburg‐Western Pomerania, Germany - Strehlow, Harry V.; Korzhenevych, Artem; Lucas, Jorrit; Lewin, Wolf‐Christian; Weltersbach, Marc Simon; Riepe, Carsten; Arlinghaus, Robert (Fisheries management and ecology, 2025)
Recreational fisheries catches are increasingly considered in the assessment and management of mixed recreational‐commercial marine fisheries, while the contribution of recreational fisheries to the economy is often overlooked. Using a telephone diary survey targeting marine recreational anglers in Germany, we estimated the number of anglers and their expenditures over the course of 1 year (2014–2015). About 197,000 marine anglers spent €248 million in Germany. We then constructed regional input–output models and contrasted the economic impacts of resident and nonresident anglers fishing in coastal and transitional brackish waters of the state of Mecklenburg‐Western Pomerania in north‐eastern Germany. On a regional scale, the total economic impact was €210 million supporting 2044 jobs, nonresident anglers were responsible for eight times greater economic impact than resident anglers. Maintaining attractive fishing opportunities for the recreational fishing sector, specifically angling tourism, is critical for maintaining resource flows to local and regional economies.